If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 5b + -3 = 2 Reorder the terms: 5 + -3 + 5b = 2 Combine like terms: 5 + -3 = 2 2 + 5b = 2 Add '-2' to each side of the equation. 2 + -2 + 5b = 2 + -2 Combine like terms: 2 + -2 = 0 0 + 5b = 2 + -2 5b = 2 + -2 Combine like terms: 2 + -2 = 0 5b = 0 Solving 5b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '5'. b = 0 Simplifying b = 0
| -62v=v+2-2 | | 4y+8c=16 | | 22.5-15+15+15=52.5+15 | | 9x-11= | | 3w+16=4 | | -4-10-x=25 | | 12y-4-6y=4 | | a-(2a-4)= | | 8y+16c=24 | | 4z+16=4 | | (16x+8x-20x+3x)= | | 8y+8c=16 | | 3xy+4xy= | | 3x+12=-2x+72 | | 3x^2-5x+16= | | 8y+8c=24 | | x^4+10x^3+35x^2+50x+24=0 | | 3y+9=24 | | 5x+2=5-2x | | 4y+4c=16 | | 6m-47=7 | | U=6v | | 3y+9c=12 | | 3y+9c=24 | | 7=6m-47 | | 3y+9c=15 | | x^3-2(x^2)+2x=400 | | 3y+9c=21 | | 69-w=173 | | 3x-19=x-15 | | 8x-2(4+x)=7 | | 2+6x-4=0 |